2018
DOI: 10.1590/rbz4720170060
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stocking density and artificial substrates on yield and water quality in a biofloc shrimp nursery culture

Abstract: The objective of this study was to evaluate the effect of different stocking densities and the presence/absence of two artificial substrates on water quality and production rates of marine shrimp in a biofloc shrimp nursery culture. Two experiments were performed: different stocking densities with mosquito netting substrate and the presence/absence of polyestertype substrate. The first experiment lasted 38 days, and shrimp at an initial weight of 0.013±0.010 g were stocked in 24 tanks. The second experiment la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
3
5
1
Order By: Relevance
“…Yield reached 1.10 kg m -3 (at 46.34 g 100 g -1 CP), which is consistent with the results of Serra et al (2015), who recorded a productivity of 1.23 kg m -3 at a density of 300 PL m -2 . However, Zhang (2011) and Legarda et al (2018) found higher rates of productivity compared to those recorded in the present study, although these results appear to be related to the higher stocking rates adopted in these studies.…”
Section: Growth Performancecontrasting
confidence: 82%
“…Yield reached 1.10 kg m -3 (at 46.34 g 100 g -1 CP), which is consistent with the results of Serra et al (2015), who recorded a productivity of 1.23 kg m -3 at a density of 300 PL m -2 . However, Zhang (2011) and Legarda et al (2018) found higher rates of productivity compared to those recorded in the present study, although these results appear to be related to the higher stocking rates adopted in these studies.…”
Section: Growth Performancecontrasting
confidence: 82%
“…These values were expected because the use of probiotics assists in improving water quality properties. In the present study, the values of the environmental factors, including temperature, pH, dissolved oxygen and salinity were within the permissible ranges in shrimp rearing ponds (Legarda et al, 2018). growth (Maia et al, 2016).…”
Section: Resultssupporting
confidence: 65%
“…By using biofloc technology, intensive shrimp culture can be carried out with reduced water usage, pathogen free and reduced waste output 23 , 24 . In shrimp, biofloc rearing has been extensively standardized with P. vannamei in terms of growth, water quality and health 8 , 9 , 13 , 25 27 . This technology can be popularized further by adopting it to other species of shrimps.…”
Section: Resultsmentioning
confidence: 99%